Analysis of the Formation of the Red and White Cabinet: Narrative Policy Framework Approach - Nugroho, Sapto Setyo; Fadiyah, Dina; Akbar, Yonarisman Muhammad; Sunarya, Amud (Ilomata International Journal of Social Science, 2025)
This study analyzes the formation of the Red and White Cabinet under President Prabowo Subianto through the lens of the Narrative Policy Framework (NPF). It examines whether the cabinet expansion was driven by technocratic considerations or political representation. This research provides insights into Indonesia’s governance structure and policymaking dynamics by exploring the narratives shaping ministerial appointments. This study employs a qualitative approach, utilizing the NPF to analyze policy narratives that influenced the expansion of ministries. Data collection involves document analysis of relevant laws, regulations, academic literature, and credible media reports. This approach systematically examines how political narratives shape institutional decisions and governance strategies. The findings reveal that the expansion of the Red and White Cabinet was primarily influenced by political coalition-building rather than administrative efficiency. Key narratives, such as governance effectiveness, political stability, and national unity, were strategically constructed to justify the increased number of ministries. While some appointments reflect technocratic expertise, many were dictated by political negotiations, highlighting the predominance of partisan interests over governance optimization. This study concludes that policy narratives legitimize political decisions, often surpassing technocratic considerations. The findings contribute to the understanding of political decision-making in Indonesia by demonstrating how institutional constraints, elite bargaining, and strategic policy narratives shape governance structures.